2020
DOI: 10.4244/eij-d-18-00496
|View full text |Cite
|
Sign up to set email alerts
|

Coronary chronic total occlusions and mortality in patients with ventricular tachyarrhythmias

Abstract: Aims: This study sought to assess the prognostic impact of coronary chronic total occlusions (CTO) in patients presenting with ventricular tachyarrhythmias on admission.Methods and results: A large retrospective registry was used, including all consecutive patients presenting with ventricular tachyarrhythmias on admission and undergoing coronary angiography from 2002 to 2016. Patients with a CTO were compared with all other patients (non-CTO) for prognostic outcomes. Statistics comprised Kaplan-Meier and Cox r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
8
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 11 publications
0
8
0
1
Order By: Relevance
“…Firstly, CTO was found in 20% of patients with ventricular tachyarrhythmias, while multiple CTO were found in 22% of these patients. The presence of a native non-revascularized CTO was significantly associated with all-cause mortality at three years, notably with increased rates of the composite endpoint of early cardiac death at 24 h, recurrent ventricular tachyarrhythmias and appropriate implantable cardioverter defibrillator (ICD) therapies [ 47 , 48 ]. A meta-analysis by Chi et al demonstrated that patients with an infarct-related CTO have a significantly higher risk of ventricular tachyarrhythmias, appropriate ICD therapy and increased all-cause mortality compared to those with a non-IRA CTO [ 49 ].…”
Section: Pathophysiologic Role Of Cto and Collateral Supply In Amimentioning
confidence: 99%
“…Firstly, CTO was found in 20% of patients with ventricular tachyarrhythmias, while multiple CTO were found in 22% of these patients. The presence of a native non-revascularized CTO was significantly associated with all-cause mortality at three years, notably with increased rates of the composite endpoint of early cardiac death at 24 h, recurrent ventricular tachyarrhythmias and appropriate implantable cardioverter defibrillator (ICD) therapies [ 47 , 48 ]. A meta-analysis by Chi et al demonstrated that patients with an infarct-related CTO have a significantly higher risk of ventricular tachyarrhythmias, appropriate ICD therapy and increased all-cause mortality compared to those with a non-IRA CTO [ 49 ].…”
Section: Pathophysiologic Role Of Cto and Collateral Supply In Amimentioning
confidence: 99%
“…From the point of view of an interventional cardiologist, less invasive SVR may be in line with another still underestimated type of PCI, the successful PCI of coronary chronic total occlusions (CTO). CTO are present in more than 20% of patients undergoing coronary angiography . Comparable to SVR, CTO‐PCI is recommended to be performed by highly skilled CTO operators in specialized centres only, where success rates of more than 90% have constantly been demonstrated.…”
mentioning
confidence: 99%
“…In contrast to SVR, CTO‐PCI is indicated for patients with relevant myocardial ischaemia in the CTO territory, which is detected in more than 95% of patients even in the presence of preserved ejection fraction and angiographically sufficient coronary collateralization. Predictors of successful CTO‐PCI are well‐described, but the potential prognostic benefit in terms of mortality reduction may even be found in patients with systolic HF and viable myocardium, without transmural scarring and severe akinesia …”
mentioning
confidence: 99%
See 2 more Smart Citations